O direito social fundamental de acesso à energia elétrica e a atuação estatal - Andrade, Maísa Medeiros Pacheco de (2009)
Electrical energy today is an essential element in the life of any human being. Through the access to electrical energy it is possible to enjoy dignified conditions of life, having in mind the possibility of making use of minimal material conditions of life. The lack of access to electricity is directly linked to poverty and degrading conditions of life, in which are some communities in Brazil, especially the more isolated from urban centers. Access to the electric service is a determining factor for the preservation of human dignity, constitutional principle inscribe in the art.1 of the Federal Constitution, and the promotion of development, being a right of everyone and a duty of the State to promote universal access. For that reason, focuses mainly on the analysis of their setting as a fundamental social right and its importance for national development. For this, the theoretical and descriptive method was used, with normative and literary analysis, in particular the Constitution of 1988. This study also discusses the form of action of the State in the energy sector, to give effect to the fundamental social right of access to electricity, the characteristics of public service and the principles that guide it, in addition to the role of public policies in universalization of access, in particular the analysis of the Program Luz para Todos, and the function of regulation in the implementation of these policies and the provision of adequate public services.